Hypothalamic amenorrhea in a Camurati-Engelmann disease – a case report†. (May 2013) - Meczekalski, Blazej; Czyzyk, Adam; Podfigurna-Stopa, Agnieszka; Rydzewski, Bogdan; Sroczynski, Jakub; Lipinska, Małgorzata; Sokalski, Jerzy; Krawczynski, Maciej; Jamsheer, Aleksander; Katulski, Krzysztof; Genazzani, Alessandro
Abstract Objective: A case report of a patient diagnosed with Camurati-Engelmann Disease (CED) in association with the functional hypothalamic amenorrhea disturbances. CED is a very rare genetically determined disorder classified as a type of bone dysplasia. Design: Case report. Setting: Department of Gynecological Endocrinology, 3rd grade Medical University Hospital. Patient: Twenty-one years old female patient with CED admitted to the hospital because of primary amenorrhea. Her history revealed skeletal deformities and hearing impairment. Methods: Clinical examination, ultrasound, laboratory evaluations (including serum gonadotropins (FSH, LH) at basal state and after stimulation with gonadotropin-releasing hormone, serum basal estradiol) radiological studies (X-ray of the head, the lumbar spine and lower extremities; a computed tomography of the head), G-banding karyotype, polymerase chain reaction and DNA sequencing. Hormonal serum evaluations were made using an enzyme-linked immunosorbent assay. The exon 4 of the transforming growth factor beta 1 gene was amplified by a polymerase chain reaction and the product was directly sequenced. Results: The hormonal analysis was characteristic for the hypogonadotropic hypogonadism. Radiological and molecular analyses confirmed CED diagnosis. Conclusions: The hypothalamic amenorrhea in a patient with CED may be explained as a consequence of fat hypotrophy and very low body mass index. Therefore, impairment within hypothalamic-pituitary axis in patients with CED should be treated with special attention.